Les enfants de la guerre : Le Grand Cahier d’Agota Kristof - Carine Trevisan (Amnis)
Starting with the study of The Notebook by Agota Kristof, this paper examines the way the state of war expels often brutally the child of its child's position, assigning him(her) a problematic place, particularly in the succession of generations. Not only witness but also often victim of the brutality of the adults, the child can nevertheless “be identified with the attacker” and become a killer too. Giving fictitiously the word to children who make the test of the brutalisation of men’s and women’s behavior in the state of war, The Notebook, by the choice of an “ice-cold” writing – this book has been qualified of “exercise of cruelty” –, led to its extreme limit the representation of devastated childhood, so much so that it becomes disturbing: abolition of any faculty to dream, to imagine, anaesthesia of emotive life, destruction of anything that can make link with others, phenomena which produce insensitivity to death, received or given. However, this loss of humanity can be regarded as a technique – certainly mutilating – of survival.